2015
DOI: 10.5901/mjss.2015.v6n5s5p34
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Macroeconomic Indicators and Foreign Ownership on Government Bond Yields: A Case of Indonesia

Abstract: The purpose of this research is to examine and analyze the influence of inflation, BI rate, exchange rate, and foreign ownership on government bond yields. Research data is monthly data from 2010 to 2013. Purposive sampling is chosen as the sampling method in this research. Based on the determined criteria, 23 government bonds have fulfilled the sample criteria. The result of this research shows that inflation, BI rate, exchange rate, and foreign ownership simultaneously have a significant influence on governm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 11 publications
(14 reference statements)
5
12
1
3
Order By: Relevance
“…These findings support the theory of the interest rate, where when interest rates increase, the bond issuer will provide higher yields [14]. The results of this study are in line with Yuliawati & Suarjaya [5], Jaramillo & Weber [16] and Kurniasih & Restika [2] who found that interest rates have a positive and significant effect on bond yields.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These findings support the theory of the interest rate, where when interest rates increase, the bond issuer will provide higher yields [14]. The results of this study are in line with Yuliawati & Suarjaya [5], Jaramillo & Weber [16] and Kurniasih & Restika [2] who found that interest rates have a positive and significant effect on bond yields.…”
Section: Resultssupporting
confidence: 91%
“…The increase in inflation in the economy will have an impact on the magnitude of risk so that the expected yield will also increase. Kurniasih & Restika [2], Yusuf & Prasetyo [3] and Hsing [4] show that inflation has a positive and significant effect on bond yields. In contrast to the research of Yuliawati & Suarjaya [5], Lumbantobing [6], and Paramita & Pangestuti [7], it shows that inflation has no effect on bond yields.…”
Section: Introductionmentioning
confidence: 99%
“…So that when liquidity is high, even though the exchange rate condition is depression, investors will invest their funds while still paying attention to the risk appetite that investors have with the high demand for bonds, it will increase bond prices and the yield will gradually decrease. The results of this study are not in line with research conducted by Kurniasih & Restika (2015) The Influence of Macroeconomic Indicators and Foreign Ownership on Government Bond Yields: A Case of Indonesia. The results of the study found that the rupiah exchange rate had a negative effect on government bond yields, but in line with Yu (2015) research on Determinant of Government Bond Yield in Spain, the exchange rate research had a positive effect on government bond yields.…”
Section: Multiple Linear Regression Model Testing Resultscontrasting
confidence: 99%
“…Penelitian (Tjandrasa, 2017) dan (Pramana & Nachrowi, 2016) menemukan suku bunga berpengaruh positif terhadap yield obligasi. Sama halnya dengan penelitian (Dhar, 2016), (Yuliani et al, 2016), (Kurniasih & Restika, 2015), (Sihombing et al, 2014), (Muharam, 2013) dan (Indarsih, 2013).…”
Section: Pendahuluanunclassified
“…(Sihombing et al, 2014) dan (Indarsih, 2013) menemukan bahwa suku bunga berpengaruh positif terhadap yield obligasi. Sama halnya (Tjandrasa, 2017), (Pramana & Nachrowi, 2016), (Dhar, 2016), (Yuliani et al, 2016), (Hsing, 2015), (Kurniasih & Restika, 2015), (Lin et al, 2011). Berdasarkan uraian diatas maka dapat diajukan hipotesis sebagai berikut:…”
Section: Pendahuluanunclassified